Economic Foundations of Society: The Historical Role of Peasants, Common Man, and Working Classes - Venkatesh Sali (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
This study investigates the economic foundations of society by tracing the historical role of peasants, the common man, and the working classes in shaping economic and social transformation. From agrarian civilizations to the rise of industrial capitalism and post-colonial development, these groups have remained the driving force behind production, distribution, and social change. Their labor sustained empires and industries, while their collective struggles challenged exploitation and redefined justice within the economic order. Grounded in economic history, Marxian political economy, and development theory, the study reveals that although technological and institutional advances have transformed modes of production, the underlying dependence on labor and surplus extraction endures. It emphasizes that peasants and workers have been both the architects and the conscience of economic progress, embodying the continuous dialectic between exploitation and empowerment. Ultimately, the research underscores that any understanding of economic development must center on these marginalized yet indispensable actors whose resilience and agency have shaped the material foundations of human civilization.